ANGIOTENSIN RECEPTOR ANTAGONISTS: GOING WITH THE TIMES - E. O. Taratukhin (Кардиоваскулярная терапия и профилактика)
This literature review focuses on the angiotensin II receptor antagonists as one of the new and promising classes of antihypertensive medications. Apart from their antihypertensive activity, these agents possess a number of other beneficial effects. The results of multiple studies, including large multi-centre clinical trials, are presented for olmesartan, an angiotensin receptor antagonist with additional beneficial properties.